Perception, Life Style and Consumer Motivation Toward Purchasing Decisions - Muhammad Yusuf; Denny Firmansyah (Enrichment : Journal of Management, 2021)
This study aims to see the effect of consumer perceptions, lifestyles, and motivations on purchasing decisions of CV Macehat Premium Coffee Beans Medan. The population is 1.340 people, with a complete sample of 93 respondents. the info analysis technique used multiple statistical regression analysis. Research data sourced from primary data with a questionnaire. supported the results of the study, it absolutely was found that the perception partially had a positive and significant effect on purchasing decisions, lifestyle partially had a positive and significant effect on purchasing decisions, and consumer motivation partially had a positive and significant influence on purchasing decisions. Perception, lifestyle, and consumer motivation simultaneously have a positive and significant impact on purchasing decisions. Adjusted R Square value of 0.952 means 95.2% of buying decisions is explained by the variables of perception, lifestyle, and consumer motivation.